utt =c2uxx=, 0<x<1
u(0,1)=0, t >0
u(1, t)=0, t >0
u(x, 0)= 2x(1-x), (0<=x <= 1)
ut (x, 0) =0
Using the variable separable method.
Let u(x,t) = X(x)T(t)
Then, the given differential equation becomes
"X(x)T''(t) = c^2X''(x) T(t)"
So we have that
"\\dfrac{1}{c^2T} \\dfrac{d^2T}{dt^2} = \\dfrac{1}{X} \\dfrac{d^2X}{dx^2}"
Using the information that
"u(0,t) = 0 = u(1,t)"
We have that the general solution is of the form
"u(x,t) = \\sum_{n=1}^{\\infty}[A_n \\cos(n\\pi c)t +B_n \\sin (n\\pi c)t] [sin(n\\pi )x]"
"u(x,0) = \\sum_{n=1}^{\\infty}A_n \\sin (n \\pi )x= 2x(1-x)"
"u_t(x,0) = \\sum_{n=1}^{\\infty} B_n n\\pi c \\sin (n \\pi )x = 0"
With
"A_n = 2 \\int_{0}^{1} 2x(1-x) \\sin (n \\pi )x dx"
And
"B_n = \\dfrac{2}{n \\pi c} \\int_{0}^{1} 0 \\sin (n\\pi )x dx = 0"
We evaluate the integral
"\\int_{0}^{1} (2x-2x^2) \\sin (n\\pi )x dx ="
"[(2x-2x^2)(\\dfrac{-1}{n\\pi} \\cos n\\pi x)]_0^1 + [(2-4x)(\\dfrac{1}{(n\\pi)^2} \\sin n\\pi x)]_0^1"
"+ \\dfrac{4}{(n\\pi)^2} \\int_0^1 \\sin (n\\pi )xdx"
"= \\dfrac{4}{(n\\pi)^3} [(-1)^{n+1}+1]"
Hence,
"A_n = \\dfrac{8}{(n\\pi)^3} [(-1)^{n+1}+1]"
But since the value of "B_n = 0"
We have that the solution with respect to the given conditions becomes
"u(x,t) = \\sum_{n=1}^{\\infty} A_n \\cos(n \\pi c)t \\sin( n \\pi )x"
where
"A_n = \\dfrac{8}{(n\\pi)^3} [(-1)^{n+1}+1]"
Comments
Leave a comment